Effect of indigenous medicinal plants on onset of puberty in immature female rats - MEHROTRA, S; SHANKER, UMA; JAWAHARLAL; MAJUMDAR, A C; AGARWAL, S K (The Indian Journal of Animal Reproduction, 2023)
Mature fresh green leaves of medicinal plants Murraya koenigii and young shoots of Urtica dioica were collected, botanically identified, shade dried, powdered and extracted with 50% ethanol under reflux. The effect of 50% ethanolic extracts of Myrraya and Urtica on onset of puberty was examined at three dose levels in immature rats i.e. I 00, 300 and I 000 mg kgI based on LD50 studies. Administration was performed orally from day 25-34 of age and induction of vaginal opening was used as an index of puberty. It was found that onset of puberty was substantially advanced aiong with body weight gain in M urraya 1000 mg kg-1 dose group.